«Kannst du’s wohl mit geschloßnen Augen denken?». La semantica del vedere nelle traduzioni italiane della «Pentesilea» di Kleist: [«Can you still visualize it when you shut your eyes?». The semantics of seeing in the Italian translations of Kleist’s «Penthesilea»] (Studia theodisca, 2024)
Starting from the centrality of the part played by the eye in Kleist’s work and, in particular, in Penthesilea, I propose to investigate how this field emerges from the Italian translations of the work. Supported by the instruments of Textsemantik (Greimas) and Texttheatralität (Poschmann) and following the comparative method (Utz), particularly significant passages from the tragedy are analysed which, in the light of this theme, pose interesting questions related to isotopy and can illuminate the differences between the translations.